Systematic development of a tennis injury prevention programme - Gino M M J Kerkhoffs; Vincent Gouttebarge; Evert Verhagen; Haiko I M F L Pas; Stefan Bodde; Babette Pluim; Ivo J H Tiemessen; Johannes L Tol (BMJ Open Sport & Exercise Medicine)
Introduction Despite an injury incidence of up to 3.0/1000 hours of play, there are no published tennis injury prevention programmes. This article aims to describe the developmental process of TennisReady, an e-health tennis-specific injury programme for adult recreational tennis players.Five-step approach A bottom-up, five-step approach was used with the Knowledge Transfer Scheme as a guideline. During the first step, a problem statement among targeted users was carried out. 475 (partially) completed surveys and group interviews (n=8) revealed a preference for an app-based prevention intervention of 10–15 min. As a second step, a systematic review was performed to identify prevention strategies in tennis. None were found. In step 3, during two expert group meetings (n=18), the findings of the first two steps were discussed and goals were formulated. Relevant and potential exercises for the programme were discussed. A subgroup of a total of six physical therapists, physicians and trainers developed the content of the programme in step 4. Step 5 included an evaluation of the exercises in 33 recreational tennis players. Participants evaluated the exercises during training sessions with trainers involved in the programme’s development or their colleagues. Participants evaluated the programme through standardised surveys or group interviews. Based on this evaluation, the programme was adjusted by altering exercises and frequencies, and it was evaluated in a second target group (n=27). The second evaluation did not result in any major changes to the final prevention programme.Conclusion Through a five-step approach guided by the Knowledge Transfer Scheme, we developed an e-health tennis-specific prevention programme for adult tennis players. This 10 min intervention will require testing in a randomised controlled setting.